Novel quinolines carrying pyridine, thienopyridine, isoquinoline, thiazolidine, thiazole and thiophene moieties as potential anticancer agents - Ghorab Mostafa M.; Alsaid Mansour S.; Al-Dosari Mohammed S.; Ragab Fatma A.; Al-Mishari Abdullah A.; Almoqbil Abdulaziz N. (Acta Pharmaceutica)
As a part of ongoing studies in developing new anticancer agents, novel 1,2-dihydropyridine 4, thienopyridine 5, isoquinolines 6–20, acrylamide 21, thiazolidine 22, thiazoles 23–29 and thiophenes 33–35 bearing a biologically active quinoline nucleus were synthesized. The structure of newly synthesized compounds was confirmed on the basis of elemental analyses and spectral data. All the newly synthesized compounds were evaluated for their cytotoxic activity against the breast cancer cell line MCF7. 2,3-Dihydrothiazole-5-carboxamides 27, 25, 4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxamide (34), 1,2-dihydroisoquinoline-7-carbonitrile (7), 5,6,7,8-tetrahydro-4H-cyclohepta[b]thiophene-3-carboxamide (35), 1,2-dihydroisoquinoline-7-carbonitrile (6), 2-cyano-3-(dimethylamino)-N-(quinolin-3-yl)acrylamide (21), 1,2-dihydroisoquinoline-7-carbonitriles (11) and (8) exhibited higher activity (IC50 values of 27–45 μmol L–1) compared to doxorubicin (IC50 47.9 μmol L–1). LQ quinolin-3-yl)-1,2-dihydroisoquinoline-7-carbonitrile (12), 2-thioxo-2,3-dihydrothiazole-5-carboxamide (28) and quinolin-3-yl)-1,2-dihydroisoquinoline-7-carbonitrile (15) show activity comparable to doxorubicin, while (quinolin-3-yl)-1,2-dihydroisoquinoline-7-carbonitrile (9), 2,3-dihydrothiazole-5-carboxamide (24), thieno [3,4-c] pyridine-4(5H)-one (5), cyclopenta[b]thiophene-3-carboxamide (33) and (quinolin-3-yl)-6-stryl-1,2-dihydroisoquinoline-7-carbonitrile (10) exhibited moderate activity, lower than doxorubicin.